The impact of the COVID-19 pandemic on final year medical students in the United Kingdom: a national survey - Byung Choi; Lavandan Jegatheeswaran; Amal Minocha; Michel Alhilani; Maria Nakhoul; Ernest Mutengesa (BMC Medical Education, 2020)
Abstract Background The coronavirus disease (COVID-19) global pandemic has resulted in unprecedented public health measures. This has impacted the UK education sector with many universities halting campus-based teaching and examinations. The aim of this study is to identify the impact of COVID-19 on final year medical students’ examinations and placements in the United Kingdom (UK) and how it might impact their confidence and preparedness going into their first year of foundation training. Methods A 10-item online survey was distributed to final year medical students across 33 UK medical schools. The survey was designed by combining dichotomous, multiple choice and likert response scale questions. Participants were asked about the effect that the COVID-19 global pandemic had on final year medical written exams, electives, assistantships and objective structured clinical examinations (OSCEs). The survey also explored the student’s confidence and preparedness going into their first year of training under these new unprecedented circumstances. Results Four hundred forty students from 32 UK medical schools responded. 38.4% (n = 169) of respondents had their final OSCEs cancelled while 43.0% (n = 189) had already completed their final OSCEs before restrictions. 43.0% (n = 189) of assistantship placements were postponed while 77.3% (n = 340) had electives cancelled. The impact of COVID-19 on OSCEs, written examinations and student assistantships significantly affected students’ preparedness (respectively p = 0.025, 0.008, 0.0005). In contrast, when measuring confidence, only changes to student assistantships had a significant effect (p = 0.0005). The majority of students feel that measures taken during this pandemic to amend their curricula was necessary. Respondents also agree that assisting in hospitals during the outbreak would be a valuable learning opportunity. Conclusions The impact on medical student education has been significant, particularly affecting the transition from student to doctor. This study showed the disruptions to student assistantships had the biggest effect on students’ confidence and preparedness. For those willing to assist in hospitals to join the front-line workforce, it is crucial to maintain their wellbeing with safeguards such as proper inductions, support and supervision.